Word Spelling Errors in Messages - Yani Lubis; Aslimah Nur; Putri Humairah Sitorus; Queen Latifa Dalimunthe (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This research aims to explore the causes, impacts and solutions related to spelling errors in written messages in more depth. With the advancement of technology, spelling mistakes can occur both unintentionally and intentionally, influenced by factors such as technological features, user habits, and social context. This research uses a descriptive qualitative method because this approach allows researchers to explore the phenomenon of spelling mistakes in written messages in depth and contextually. The results show that spelling errors are often caused by inaccurate autocorrect features, small keyboard size, and time pressure when sending messages. In formal contexts, spelling errors can lower the credibility of the message sender and cause confusion in comprehension. To reduce such errors, this study recommends the development of smarter autocorrect systems and digital literacy education to improve the quality of communication.